Habituals in Spanish (Linguistics in Amsterdam, 2021)
In this paper, we discuss two constructions that are used in the expression of habituality in Peninsular Spanish: one involving the Imperfecto verb form, the other the periphrastic construction consisting of the auxiliary verbs soler or acostumbrar (a) followed by the infinitive. After presenting the basic properties of these constructions, we address the question what determines the choice between the two strategies. We show that in habitual contexts the Imperfecto is used, unless the storyline is interrupted and a habit is presented as background information, or when pragmatic highlighting of the habit is involved. In these cases, the periphrastic construction is required. In non-habitual contexts the periphrastic construction is the only strategy available for the expression of habituality.